Flavopiridol can be safely administered using a pharmacologically derived schedule and demonstrates activity in relapsed and refractory non‐Hodgkin's lymphoma. Issue 1 (30th September 2013) - Jones, Jeffrey A.; Rupert, Amy S.; Poi, Ming; Phelps, Mitch A.; Andritsos, Leslie; Baiocchi, Robert; Benson, Don M.; Blum, Kristie A.; Christian, Beth; Flynn, Joseph; Penza, Sam; Porcu, Pierluigi; et al.
<x xml:space="preserve">Abstract</x> Flavopiridol is a broad cyclin‐dependent kinase inhibitor (CDKI) that induces apoptosis of malignant lymphocytes in vitro and in murine lymphoma models. We conducted a Phase I dose‐escalation study to determine the maximum tolerated dose (MTD) for single‐agent flavopiridol administered on a pharmacokinetically derived hybrid dosing schedule to patients with relapsed and refractory non‐Hodgkin's lymphoma. Dose was escalated independently in one of four cohorts: indolent B‐cell (Cohort 1), mantle cell (Cohort 2), intermediate‐grade B‐cell including transformed lymphoma (Cohort 3), and T‐/NK‐cell excluding primary cutaneous disease (Cohort 4). Forty‐six patients were accrued. Grade 3 or 4 leukopenia was observed in the majority of patients (60%), but infection was infrequent. Common nonhematologic toxicities included diarrhea and fatigue. Biochemical tumor lysis was observed in only two patients, and no patients required hemodialysis for its management. Dose escalation was completed in two cohorts (indolent and aggressive B‐cell). Dose‐limiting toxicities were not observed, and the MTD was not reached in either cohort at the highest dose tested (50 mg/m2 bolus + 50 mg/m2 continuous infusion weekly for 4 consecutive weeks of a 6‐week cycle). Clinical benefit was observed in 26% of 43 patients evaluable for response, including 14% with partial responses (two mantle cells, three indolent B‐cells, and one diffuse large B‐cell). The single‐agent activity of this first‐generation CDKI suggests that other agents in this class merit further study in lymphoid malignancies, both alone and in combination. Am. J. Hematol. 89:19–24, 2014. © 2013 Wiley Periodicals, Inc.